2014
DOI: 10.1007/s12264-014-1483-7
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 4-mediated nuclear factor-κB activation in spinal cord contributes to chronic morphine-induced analgesic tolerance and hyperalgesia in rats

Abstract: Nuclear factor kappa B (NF-κB) in the spinal cord is involved in pro-infl ammatory cytokine-mediated pain facilitation. However, the role of NF-κB activation in chronic morphine-induced analgesic tolerance and the underlying mechanisms remain unclear. In the present study, we found that the level of phosphorylated NF-κB p65 (p-p65) was increased in the dorsal horn of the lumbar 4-6 segments after intrathecal administration of morphine for 7 consecutive days, and the p-p65 was co-localized with neurons and astr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 47 publications
(61 reference statements)
1
42
1
Order By: Relevance
“…MMP-9 has been proven to cleave IL-1β, which is one of the most important pro-inflammatory cytokines in nervous system and promotes the development of opioid-induced tolerance and hyperalgesia [33]. Our data demonstrated that intraoperative remifentanil infusion induced the up-regulation of mature active IL-1β in both DRG neurons and SGCs, and NAC decreased remifentanil-induced IL-1β activation via inhibiting MMP-9.…”
Section: Discussionmentioning
confidence: 61%
“…MMP-9 has been proven to cleave IL-1β, which is one of the most important pro-inflammatory cytokines in nervous system and promotes the development of opioid-induced tolerance and hyperalgesia [33]. Our data demonstrated that intraoperative remifentanil infusion induced the up-regulation of mature active IL-1β in both DRG neurons and SGCs, and NAC decreased remifentanil-induced IL-1β activation via inhibiting MMP-9.…”
Section: Discussionmentioning
confidence: 61%
“…Astrocytes and microglia are activated after chronic morphine treatment in mice spinal cord789, and the activated glias can increase the release of pro-inflammatory cytokines such as TNF-α and IL-1β101112 to further promote the development of morphine tolerance. The western blot results showed that the levels of GFAP (an astrocytic marker), IBA1 (a microglial marker) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Chronic morphine treatment can significantly increase the release of different neurotransmitters such as glutamate (Glu), which binds to the NMDA receptor to enhance the excitatory synaptic transmission56. It also activates the astrocytes and microglia789, leading to the release of the pro-inflammatory cytokines such as tumor necrosis factor-α (TNFα) and interleukin-1β (IL-1β)101112 to promote the morphine tolerance.…”
mentioning
confidence: 99%
“…Western blotting was performed according to our published procedures [30,31]. Briefly, the animals were sacrificed by decapitation and the L4-5 spinal dorsal horns were harvested and placed temporarily in liquid nitrogen.…”
Section: Western Blottingmentioning
confidence: 99%